2023
DOI: 10.1155/2023/7868392
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Family Caregivers in the Caring for COVID-19 Patient: Self-Sacrificing Management, Fear, and Loneliness to Protect the Patient—A Qualitative Content Analysis

Abstract: This study aimed to evaluate the perception of family caregivers in the care process of patients with COVID-19. This study was conducted on 19 family caregivers, who were selected using purposive sampling from 2021 to 2022. Unstructured interviews were used to collect data. The data were analyzed using the Kyngas conventional content analysis approach. The analysis of data led to three main themes, including unremitting efforts in physical care in the light of traditional medicine, accuracy, and intelligence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
1
0
2
Order By: Relevance
“…The study identified changes in caregivers' physical and mental health needs. Constant vigilance due to shared accommodations, fear of contracting the virus, financial burden, unfulfilled roles, stigma, and inefficient management led to negative emotions such as fear, anxiety, helplessness, and burnout, consistent with previous studies [33][34][35]. Early psychological intervention is crucial to promoting emotional release and mental well-being among caregivers during epidemics.…”
Section: Discussionsupporting
confidence: 83%
“…The study identified changes in caregivers' physical and mental health needs. Constant vigilance due to shared accommodations, fear of contracting the virus, financial burden, unfulfilled roles, stigma, and inefficient management led to negative emotions such as fear, anxiety, helplessness, and burnout, consistent with previous studies [33][34][35]. Early psychological intervention is crucial to promoting emotional release and mental well-being among caregivers during epidemics.…”
Section: Discussionsupporting
confidence: 83%
“…Según Faghani, Ahmadi y Mohammadi 23 , su estudio, además de poner en cuarentena a los pacientes y retirar sus efectos personales, los cuidadores hacen un gran esfuerzo para desinfectar el equipo, especialmente los utensilios, platos, inodoros y baños del paciente, la ropa de cama del paciente e incluso el piso de la habitación para evitar que el virus se propague y mejorar los síntomas de los pacientes eliminando su recontacto con el virus. Además, los cuidadores utilizaron diversos desinfectantes y limpiadores, como alcohol, lejía y vinagre, para limpiar el hogar, el inodoro, el baño y el equipo del paciente para evitar la propagación del virus tanto en el paciente como en el hogar.…”
Section: Discussionunclassified
“…Dentro de los cuidados que realizaron fueron, brindar alimentos como el extracto de cuy, pichón, gallina, por la cantidad de proteínas que estos animales contienen, y a su vez alimentos líquidos y/o poco consistentes como licuados bajos en sal para su fácil digestión; por otro lado, en lo que respecta a la higiene, los baños fueron con esponja o pañitos húmedos realizados con agua tibia sin movilizarlo a una ducha, siendo este el cuidado de aseo que se les brindó desde el inicio con COVID-19; a su vez estos tuvieron que aprender sobre la toma y vigilancia de los signos vitales y el estado del familiar delicado, siendo este un evento esencial para alertar en la etapa en la cual pueda empeorar el paciente con COVID-19. Frente a esta realidad de la pandemia vivida por la COVID-19, los familiares se convirtieron en cuidadores de los pacientes contagiados atendidos en casa, brindándoles así un cuidado integral y humanizado ante este terrible momento para ambos22 .En un estudio similar de Faghani, Ahmadi y Mohammadi23 . resalta que muchos cuidadores utilizaron una dieta nutritiva adecuada para estimular el sistema inmunológico del paciente, por lo que les brindaron bebidas como té ligero, alimentos como el pescado y pollo a la parrilla, cocinaron verduras como las espinacas, tomaron mucho más en cuenta las frutas y eliminaron los dulces, del mismo modo los familiares mencionaron el uso de remedios a base de hierbas por varias razones, entre ellas incluía la mejora de varios síntomas de la enfermedad y el aumento del efecto de los medicamentos químicos en el tratamiento de COVID-19.…”
unclassified
“…COVID-19 outbreak created many public mental health concerns and with many possibly unknown dimensions, this disease not only disrupted the lives of COVID-19 patients but also the caregivers caring them (9).Caregiving is a process of undertaking the activities and responsibilities of caregiving which involves different types of support like emotional, physical, and financial support (10). Because of lack of formal type of caregiving in Nepal, major responsibility of caregiving is shouldered by family members who are also referred to as informal caregivers (11).…”
Section: Introductionmentioning
confidence: 99%